The shape of thunder - Warga, Jasmine (Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
Estranged from the best friend whose brother killed her sister in a school shooting, a grieving Cora receives a message on her twelfth birthday from her friend, asking for her help with creating a time portal to prevent the tragedy.